CONVENIENT FUNERAL OF « TOPOKE » PEOPLE IN THE COMMON MANGOBO IN KISANGANI : VIOLATIVE FACTS IN CONGOLESE RIGHT. - ASAKA John, ANGONDO; Esaïe BESINGELA BOLOMBI; Prosper IDJUMBE WOLA; Elise KASONGO WALO; Laurent BAMBALE BOTANDO (IJRDO - Journal of Social Science and Humanities Research, 2019)
The present survey is about the funeral practices in general in the city of Kisangani and in the common Mangobo in particular. He/it is question to study the behaviors, the attitudes, the constructions cultural of the roles, the customary practices that organize themselves at the time of ceremonies of the funeral, that are altered today. He/it observes himself/itself in the common Mangobo of the funeral practices that lets to want to the look of their consequences on the future generations. It is also the case of obscene dances that looks well like the non admitted spectacles children.   The transportation of the deadly remains in Mangobo doesn't make itself on board of a hearse or another suitable transportation means, but the remains is transported to 80% to the shoulders of the young people. All along the road, the funeral cortege executes songs to the immoral content while having fun with the body to the risk to make fall it.  Where the mourning is organized, there are people, in most cases that come in a state of insobriety that plays musics non adapted to the circumstance, the volume of the too strong music to break the eardrum.   The behaviors as described high here constitute some infringements altogether to the look of sla Congolese legislation.   There is grounds to understand, through the present survey, the reasons of the non eradication of these practices contrary to the Congolese positive right. From where an anthropological survey combined to the legal survey is indispensable in order to put a term to these practices Contra legem.